The prevalence and predictors of anxiety and depression in near-centenarians and centenarians: a systematic review. (29th July 2019) - Cheng, Adrian; Leung, Yvonne; Harrison, Fleur; Brodaty, Henry
ABSTRACT: Background: Current research on the psychological health of near-centenarians (95−99 years old) and centenarians remains limited. Existing studies have mainly characterized their physical, cognitive, and social health. Results on the anxiety and depression of near-centenarians and centenarians (more than 95 years old) have been mixed with some studies, finding higher rates of anxiety and depression among those older than 95 years and others reporting no difference in rates compared with younger age groups. This study aims to synthesize the existing literature on the prevalence and predictors of anxiety and depression in near-centenarians and centenarians. Method: A systematic review was conducted using Ovid Medline, Embase, PsycINFO, CINAHL, SCOPUS, and the Cochrane database. Common and conflicting findings among the literature were examined. Results: Thirty-eight studies met the inclusion criteria. Six studies examined the prevalence and predictors of anxiety, and 37 studies investigated the prevalence and predictors of depression. Five studies examined both anxiety and depression in the same sample. Prevalence data on anxiety and depression varied significantly, as did comparisons with rates in younger populations. Findings on predictors of anxiety and depression were contradictory. Conclusion: There is a large degree of heterogeneity among studies of centenarians' psychological status. Findings conflict on the prevalence and predictors of anxiety and depression and rates compared with younger age groups. Variation in findings may result from the different inclusion criteria, sampling methods, and measurement tools. Better harmonization of centenarian study methodologies may improve consistency of findings to aid in developing clinical interventions.